Does the new government-business relations improve corporate environmental performance? A perspective based on environmental regulatory capture - Guo, Bingnan; Zhan, Baoliang; Hu, Peiji; Liu, Tangfa (Frontiers in Environmental Science, 2024)
IntroductionGovernment-business relations are a concentrated manifestation of the interaction process and outcomes between the government and enterprises, directly influencing the social capital and institutional environment upon which businesses rely. Sound government-business relations are crucial for addressing environmental issues and promoting high-quality development in China.MethodsThis study extensively examines how New Government-business Relations (NGR) impact Corporate Environmental Performance (CEP) by analyzing A-share listed companies from 2017 to 2021 and applying the regulatory capture theory.ResultsThe empirical findings show that NGR can prevent environmental regulatory capture, thereby improving CEP. After conducting several robustness tests, such as substituting the dependent variable, using instrumental variables, and performing dynamic panel analysis, the results remain consistent. Additionally, the mechanism analysis reveals that NGR can effectively thwart environmental regulatory capture resulting from rent-seeking behavior and political connections, leading to enhanced CEP. Moreover, additional research indicates that the beneficial impact of the NGR on the environmental performance of non-high-pollution industry enterprises, mature enterprises, and businesses operating in regions with stringent environmental regulations is more significant.DiscussionBuilding on prior literature, this paper augments the body of relevant research on environmental regulatory capture within the Chinese context, offering fresh insights and empirical evidence to comprehend the evolving government-business relations in contemporary times and their significance in environmental conservation.